Evaluation of the effects of gait training on the device Lokomat in children with Cerebral Palsy. Preliminary Report - Flis, Dominika; Kwolek, Andrzej; Rusek, Wojciech (European Journal of Clinical and Experimental Medicine, 2015)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The aim of the research. The aim of research was to esteem the results of re-education of the gait in children with Cerebral Palsy in conditions of dynamic load on the Locomat. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Materials and method. 11 patients with spastic cerebral palsy, participating in the gait training, were examined. 6 children were diagnosed to have four-limb paralysis, 5 children were diagnosed to have bilateral spastic paresis. The average age of the examined children was 9 years. Every patient was examined after 10 therapy sessions. The level of child’s motor disability was estimated according to Kudrjavcev scale and GMFCS scale, the balance was estimated according to Berg Scale, the gait according to Wisconsin Gait Scale. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The improvement could be observed for all the children who had been checked, the range of improvement was diverse. The gait improvement was better for children with bilateral spastic paresis. The essential statistical difference in the balance effects esteem between two groups of examined children was not stated. The gait improvement for all children.The best improvement was in the hip movement during transfer of appropriate, the knee joint bending and the fear of reflection diminished. The balance improved for all children, the best change was in the range of standing without support, reaching forward and the ability of body changing. More therapy sessions helped obtain better therapy results. Children of ,,bigger risk” present weaker abilities to compensate for. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions. The gait of children improves in the individual way, it can be proved by the fact that children with Cerebral Palsy present diverse abilities to compensate for. The gait training contributes to the life independence increase, the therapy result depends on the clinic state of cerebral palsy and the initial functioning state of the child at the beginning of the therapy.